The synergetic effect of selenium or zinc oxide nanoparticles with chromium on mitigating thermal stress for sustainable production and improving antioxidant capacity and inflammatory cytokines of growing rabbits - I. T. El-Ratel; K. H. El-Kholy; S. M. Elgmmal; S. F. Fouda; A.-K. E. Abdel-Khalek; M. A. Hassan; M. M. Azzam; M. Alagawany; A. Lestingi (Archives Animal Breeding, 2025)
This study was conducted to evaluate the impacts of selenium nanoparticles (SeNPs), zinc oxide nanoparticles (ZnONPs), and a combination of SeNPs and chromium (Cr) or ZnONPs and Cr on growth, caecal microbiota, antioxidant capacity in blood and liver tissue, and inflammatory cytokines in heat-stressed rabbits. A total of 100 newly weaned APRI rabbits were randomly divided into five homogeneous groups. A basal diet containing no feed additives (0 g per kg diet) was given to the first group, and the second, third, fourth, and fifth groups were given a diet supplemented with 0.3 mg SeNPs, 20 mg ZnONPs, 0.3 mg SeNPs and 1.5 mg Cr, and 20 mg ZnONPs and 1.5 mg Cr per kg diet, respectively. At 10 and 14 weeks of age, the live body weight (LBW) of rabbits was higher (P < 0.05) in all treatments, while LBW at 10 weeks of age was higher (P < 0.05) in combination groups. All treatments increased daily body weight gain in the age intervals of 6–10 and 6–14 weeks (P<0.05). Daily body weight gain was increased (P < 0.05) in combination groups at the age interval of 6–10 weeks. Feed intake was only increased for rabbits in the ZnONP–Cr group at age intervals of 10–14 weeks. The feed conversion ratio was significantly improved in all treatments at 6–10 and 6–14 weeks of age compared to the control. Haemoglobin was increased (P<0.05) in diets supplemented with ZnONPs and SeNP–Cr or ZnONP–Cr combinations. The platelet count was only increased (P < 0.05) by the ZnONP–Cr combination compared to other groups. Serum total proteins, total antioxidant capacity, superoxide dismutase, glutathione peroxidase, IgA, IgM, nitric oxide, and lysozyme were increased, while serum total cholesterol and triglycerides, alanine transaminase, malondialdehyde, myeloperoxidase, tumour necrosis factor (TNF-α), and interleukin 4 (IL-4) were reduced by all treatments. The total antioxidant capacity in liver tissue was higher, and malondialdehyde was lower in all treatment groups. Albumin was significantly increased, while glucose, creatinine, and urea were significantly decreased in response to ZnONPs and SeNP–Cr or ZnONP–Cr combinations compared with the other groups. Dietary addition of SeNPs–Cr or ZnONPs–Cr significantly reduced interferon-gamma (IFN-γ) concentration. The caecal activity was increased, while the Escherichia coli (E. coli) count decreased considerably in all treatments compared to the control. In conclusion, SeNPs or ZnONPs with chromium as trace elements of growing rabbits can be recommended as an effective intervention to mitigate the negative impacts of heat stress (HS) by enhancing growth performance, promoting metabolic processes, and boosting immunity.